Epidermolysis bullosa hereditaria letalis - Say, Burhan; Marulyalı, Keriman (The Turkish Journal of Pediatrics, 1959)
A case of epidermolysis bullosa hereditaria letalis, admitted to the Hacettepe Children’s Hospital at 11 hours of age, has been presented and is the first such case reported in Turkey. A brief review of the history, theories of etiology, and classifications, and a discussion of various forms of therapy have been presented.